Новий герой сучасної воєнної прози (на матеріалі книжок про Майдан та війну на Донбасі) - Герасименко, Н. (Слово і Час, 2020)
У статті розглянуто нові твори з карколомними сюжетами й несподіваними розв'язками, присвячені подіям Революції гідності й російсько-українській війні на Сході України. Окрім спільної теми, книжки, що вийшли
друком у 2014—2018 рр., засвідчили появу нового героя — освіченого молодого чоловіка з міцною проукраїнською позицією. Зараз він зі зброєю в руках боронить на Донбасі свою Батьківщину, свій вибір і майбутнє. The events on Maidan, the Russian-Ukrainian war in the East of Ukraine became a particular
challenge not only for the novice writers but also for the famous masters of the
word. Some of them took part in the defense of the country; others were strictly focused
on the contemporary situation and talked with the soldiers who returned from the front.
New works with scary stories and unexpected solutions aroused. In addition to the common
theme, these books, published in 2014–2018, showed another common longed-for
phenomenon – the emergence of a new hero. He is a patriot who, with weapons in hands,
defends the homeland in Donbas, his own choice and future. He is a well-educated young
man with a strong pro-Ukrainian position who is proud of his nationality. He has the power
to design and successfully conduct a military special operation. Now he is ready for changes
within society, he is savvy in questions of politics and course of Ukraine in the international
arena. He is characterized by determination and perseverance, he is ready to fight. The new
hero does not trust the central government since during all the years of independence it
demonstrated to its own people only political weakness and double standards.
An ordinary Ukrainian might be used to adjust himself to all the authorities without
exception. However, the events of Maidan, and then the war woke up the society and swept
its apathy. The desire to defend oneself, one’s family and friends, and the whole country gave
strength to the people. Thus a new, self-confident and strong Ukrainian became typical. He
is a leader able to motivate his comrades for being active in the battlefield and politics. The
new hero may have even some messianic features corresponding to the people’s expectations.